Fine particulate matter air pollution and aortic perivascular adipose tissue: Oxidative stress, leptin, and vascular dysfunction. Issue 15 (29th July 2021) - Haberzettl, Petra; Jin, Lexiao; Riggs, Daniel W.; Zhao, Jingjing; O'Toole, Timothy E.; Conklin, Daniel J.
Abstract: Exposure to fine particulate matter (PM2.5 ) air pollution increases blood pressure, induces vascular inflammation and dysfunction, and augments atherosclerosis in humans and rodents; however, the understanding of early changes that foster chronic vascular disease is incomplete. Because perivascular adipose tissue (PVAT) inflammation is implicated in chronic vascular diseases, we investigated changes in aortic PVAT following short‐term air pollution exposure. Mice were exposed to HEPA‐filtered or concentrated ambient PM2.5 (CAP) for 9 consecutive days, and the abundance of inflammatory, adipogenic, and adipokine gene mRNAs was measured by gene array and qRT ‐ PCR in thoracic aortic PVAT. Responses of the isolated aorta with and without PVAT to contractile (phenylephrine, PE) and relaxant agonists (acetylcholine, ACh; sodium nitroprusside, SNP) were measured. Exposure to CAP significantly increased the urinary excretion of acrolein metabolite (3HPMA) as well as the abundance of protein–acrolein adducts (a marker of oxidative stress) in PVAT and aorta, upregulated PVAT leptin mRNA expression without changing mRNA levels of several proinflammatory genes, and induced PVAT insulin resistance. In control mice, PVAT significantly depressed PE‐induced contractions—an effect that was dampened by CAP exposure. Pulmonary overexpression of extracellular dismutase (ecSOD‐Tg) prevented CAP‐induced effects on urinary 3HPMA levels, PVAT Lep mRNA, and alterations in PVAT and aortic function, reflecting a necessary role of pulmonary oxidative stress in all of these deleterious CAP‐induced changes. More research is needed to address how exactly short‐term exposure to PM2.5 perturbs PVAT and aortic function, and how these specific genes and functional changes in PVAT could lead over time to chronic inflammation, endothelial dysfunction, and atherosclerosis. Abstract : Short‐term (9‐day) exposure of mice to concentrated ambient particulate matter (CAP) alters the function of perivascular adipose tissue (PVAT) and aorta. Short‐term CAP exposure increased PVAT oxidative stress and leptin mRNA. Normally, PVAT and endothelium are anticontractile and modulate aortic vascular smooth muscle (VSMC) tone. After CAP exposure, however, the aorta becomes more contractile with accompanying loss of endothelial‐dependent modulation and increased PVAT‐dependent anticontractile function. The increased PVAT leptin may represent a compensatory response to maintain vascular tone balance. The CAP‐induced alterations in pulmonary and systemic oxidative stress, leptin mRNA abundance in PVAT, and aortic contractility were prevented in mice overexpressing pulmonary extracellular superoxide dismutase (ecSOD‐Tg) implicating pulmonary oxidative stress in CAP‐induced changes.